Injury Therapy Program Reduce Pain Scale on Knee Injury at Jogja Sports Clinic - Muhammad Azzam Ayyasy; Anies Setiowati; Sri Surmartiningsih; Aziz Amrulloh; Sugiarto Sugiarto (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2023)
Health is desired by everyone because it enables individuals to live socially and economically productive lives. Injuries can hinder daily activities, therefore appropriate actions are needed to facilitate recovery. The purpose of this study is to determine the effectiveness of injury therapy programs (manual therapy, electrical therapy, and cold therapy) on reducing pain in knee injuries at Jogja Sports Clinic.The research method used is a quasi experiment one-group pre-test post-test design. The research sample was obtained through purposive sampling, which included patients at Jogja Sports Clinic who met the inclusion criteria. The independent variable in this study is the injury therapy program, which includes manual therapy using massage, electrical therapy using TENS, and cold therapy using ice compresses. The dependent variable is pain perception, which is measured using a visual analog scale (VAS). Data analysis techniques use paired t tests, which has passed the prerequisite tests for normality and homogeneity.The average VAS pretest result of n=15 research subjects is 7, while the average VAS posttest result of n=15 is 2. Using paired t-test with the assistance of SPSS version 27 application, the significance value (2-tailed) is 0.001. Paired t-test is considered effective when the sig. value (2-tailed) < 0.05.The study that concluded the injury therapy program consist of massage, TENS, and cold compression with 3 sessions per week for 2 weeks, effectively reduced knee pain in Jogja Sports Clinic by 71%. The recommendation given for further research is to pay attention to the limitations within the study and the need to increase the sample size in order to obtain more optimal results.